Causes Of Low Hemoglobin Levels In Pregnancy - Elsy Putri Parwati; Ratna Wardani (Universitas STRADA Indonesia, 2019)
Low levels of hemoglobin in pregnancy have become a major health problem today as it affects nearly half of the population of pregnant women worldwide. Anemia in pregnant women is caused by several causes, namely iron deficiency and compliance with Fe consumption during pregnancy is not routine. Efforts used to reduce the rate of anemia in pregnant women are by giving iron supplements during pregnancy. Health workers need to provide health education about the importance of nutrition for pregnant women to prevent anemia during pregnancy. The aim is to determine the causes of the incidence of low hemoglobin in pregnancy. This type of study is literature (Literature review). The literature sources used are journals from Pubmed, Research Gate and Google Scholar. The causes of low hemoglobin incidence were adherence to drinking iron tablets, ANC, age, and parity, protein and vitamin C, knowledge, attitudes and behavior in consuming iron / Fe tablets. Adequate intake of iron or iron, protein, vitamin C is essential for a healthy pregnancy. It is necessary to pay attention to age, parity, knowledge, attitudes, consumption behavior during pregnancy fe.